The Effect of Leverage, Profitability and Institutional Ownership on Tax Management with Company Size as a Moderating Variable (Case Study on Mining Companies Listed on the IDX in 2021-2023) - Pitriani, Anisa; Sabaruddin, Sabaruddin (Dinasti Publisher, 2025)
This study aims to analyze the effect of leverage, profitability and institutional ownership on tax management using company size as a moderating variable. The population of this study is all mining companies listed on the IDX in 2021-2023. Based on purposive sampling, 20 mining companies were used as samples in this study. This study is a quantitative study with descriptive statistical methods. The data in this study were processed using E-Views software. The results of the study indicate that leverage, profitability and institutional ownership have no effect on tax management. Company size can only moderate the effect of leverage on tax management. Company size weakens the effect of profitability on tax management. Company size cannot moderate the effect of institutional ownership on tax management. Company size can moderate the effect of leverage, profitability and institutional ownership on tax management.